Associations of multiple domains of self-esteem with four dimensions of stigma in schizophrenia - Lysaker, Paul H. (2007)
Research suggests global self-esteem among persons with schizophrenia may be negatively affected by stigma or stereotyped beliefs about persons with severe mental illness. Less clear however, is whether particular dimensions of self-esteem are linked to particular domains of stigma. To examine this we surveyed a range of self-esteem dimensions including lovability, personal power, competence and moral self-approval and four domains of stigma: Stereotype endorsement, Discrimination experience, Social withdrawal and Stigma rejection. Participants were 133 adults with diagnoses of schizophrenia or schizoaffective disorder. Stepwise multiple regressions controlling for a possible defensive response bias suggested that aspects of self-esteem related to lovability by others were more closely linked with lesser feelings of being alienated from others due to mental illness. Aspects of self-esteem related to the ability to manage one’s own affairs were more closely associated with the rejection of stereotypes of mental illness. A sense of being able to influence others was linked to both the absence of discrimination experiences and the ability to ward off stigma. Implications for treatment are discussed.